'My wife converted me': Gendered values and gendered conversion in Pentecostal households in Honiara, Solomon Islands. (24th April 2016) - Maggio, Rodolfo
Abstract : Church organization, the notion of person, and the charismatic discourse on value in Pentecostal denominations deeply influence gender relations among church members. In turn, gender relations influence the ways in which the charismatic discourse is received and concretised. My analysis explores this complex process of mutual transformations of gender roles and conversion meanings among Pentecostal Christians in an illegal settlement on the outskirts of Honiara, Solomon Islands. In particular, I focus on how husband and wife in Pentecostal households change the way they look at each other as they undertake a process of charismatic renewal. My aim is to illustrate how the statement of a Kwara'ae man reveals the meaning of conversion as a long‐term process that takes place relationally and under the influence of gendered values.